Associations between adverse childhood experiences and medical students’ interest in careers: a single-setting study - Yang, Phillip; Robles-Ramamurthy, Barbara; Plastino, Kristen A. (Frontiers in Psychiatry, 2025)
BackgroundAdverse childhood experiences (ACEs) are pervasive across communities, including medical students and physicians. Exposure to childhood trauma influences career decisions, such as social workers and nurses. However, the impact of ACEs on medical students’ career interests remains unexplored.MethodsFrom August to October 2022, a survey was designed and administered to medical students at UT Health San Antonio School of Medicine (Texas, USA). Ten household-level and four community-level ACEs were assessed. Associations between ACE distribution and interest in medical specialties, academia, and primary care were analyzed by Mann-Whitney U test.ResultsFour hundred nineteen (47.0%) of 891 total students completed the survey, of which 310 (74.3%) reported at least one ACE and 107 (25.7%) reported four or more. The most common ACE was living with a household member with mental illness (154, 36.9%). Students interested in psychiatry (p<.01) or academic medicine (p=.02) had significantly higher ACE scores than those not interested in these fields. No associations were observed between ACEs and students’ interest in primary care.DiscussionThe prevalence of medical students living with a household member with mental illness was approximately double than reported in population-based studies. Childhood trauma exposure may influence medical students’ interests in psychiatry and academic medicine careers. Further research is needed to investigate how ACEs influence medical students’ career considerations. Research exploring ACEs exposure in academic physicians and psychiatrists may further illuminate the associations found in this brief report. Importantly, advancements in trauma-informed approaches to medical education are necessary to facilitate safe learning environments.